FAMILY RANGOMARAMIDAE - Falaschi, Rafaela Lopes; Amorim, Dalton De Souza (Zootaxa, 2016)
This small family of Diptera is poorly known in Colombia. In the present catalogue, we feature a single report for the country, of a species of the genus Eratomyia.